Research on Social Anxiety Level and Communication Skills of Secondary School Students - KOÇ, Mustafa; DÜNDAR, Aykut (Asian Journal of Education and Training, 2018)
The aim of his study is to examine the social anxiety level and communication skills of secondary school students in terms of some variables. A total of 382 students, 192 males and 190 females attending the secondary education institutions of the province Adıyaman in the academic year 2016-2017, participated in the study. The scale developed by Özbay and Palancı (2001) to measure the social anxiety level of the students and the scale developed by Korkut (1997) to measure communication skills were used. In the analysis of the data, the statistical package program was used. T-test and variance analysis (ANOVA) were used in independent groups, Post Hoc Tukey test was used for the differences between groups and Pearson correlation test was used for finding relationship; error level is obtained as 0,01 and 0,05. As a result of the research, there was no significant difference was found in social anxiety and communication skills in terms of the students' genders and the fact that whether they do sports or not. A statistically significant relationship was found between the communication skills of the individuals and their social anxiety scores in the strong negative direction. It was seen that the students with more communication skills had lower social anxiety scores. A statistically significant relationship was found in the strong positive direction between the students' social anxiety level and social anxiety sub-scale scores. A statistically significant relationship was found in the positive direction between the students' communication skills and communication skills sub-scale scores.